Assessment of the antinociceptive, respiratory-depressant, and reinforcing effects of the low pK a fluorinated fentanyl analogs, FF3 and NFEPP - Edwards, Shelley R; Blough, Bruce E; Cowart, Kristian; Howell, Grace H; Araujo, Aaron A; Haskell, Jacob P; Huskinson, Sally L; Rowlett, James K; Brackeen, Marcus F; Freeman, Kevin B (Neuropharmacology, 2024)
Recent studies report that fentanyl analogs with relatively low pK values produce antinociception in rodents without other mu opioid-typical side effects due to the restriction of their activity to injured tissue with relatively low pH values. However, it is unclear if and to what degree these compounds may produce mu opioid-typical side effects (respiratory depression, reinforcing effects) at doses higher than those required to produce antinociception. The present study compared the inflammatory antinociceptive, respiratory-depressant, and reinforcing effects of fentanyl and two analogs of intermediate (FF3) and low (NFEPP) pK values in terms of potency and efficacy in male and female Sprague-Dawley rats. Nociception was produced by administration of Complete Freund's Adjuvant into the hind paw of subjects, and antinociception was measured using an electronic Von Frey test. Respiratory depression was measured using whole-body plethysmography. Reinforcing effects were measured in self-administration using a progressive-ratio schedule of reinforcement. The dose ranges tested for each drug encompassed no effect to maximal effects. All compounds produced full effects in all measures but varied in potency. FF3 and fentanyl were equipotent in antinociception and self-administration, but FF3 was less potent than fentanyl in respiratory depression. NFEPP was less potent than fentanyl in every measure. The magnitude of potency difference between antinociception and other effects was greater for FF3 than for NFEPP or fentanyl, indicating that FF3 had the widest margin of safety when relating antinociception to respiratory-depressant and reinforcing effects. Low pK fentanyl analogs possess potential as safer analgesics, but determining the optimal degree of difference for pK relative to fentanyl will require further study due to some differences between the current results and findings from prior work with these analogs.